Effects of 8 weeks parent-accompanied swimming on physical capacity and intelligence in preschool children - Yu, Yichao; Xia, Lei; Yan, Huiping; Lu, Yifan (Frontiers in Public Health, 2024)
This study aimed to explore the potential effects of 8-week parents-accompanied swimming on the physical capacity and intelligence of preschool children in China. Thirty-six boys (mean age 3.56 ± 0.27 years) were divided into three groups: the traditional physical exercise group (TP, n=12), the accompanied swimming group (AS, n=12) and the independent swimming group (IS, n=12). Participants' physical capacity was assessed before and after the intervention using the following indicators: height, weight, distance of tennis ball throw, standing long jump distance, time for the 10-meter shuttle run, time for a two-legged continuous jump, sit-and-reach distance, and time on the walking balance beam. Intelligence was assessed at three points: pre-test, mid-test after 4 weeks, and post-test. Data were analyzed using a two-way repeated measures ANOVA, Bonferroni test (P < 0.05) and effect size. The time of the AS and IS groups to walk the balance beam was significantly lower than the TP group, with a difference of 1.81s (P < 0.01, [95% CI -3.22 to -0.40], ES = 1.53) and 1.25s (P < 0.05, [95% CI -2.66 to 0.16], ES = 0.81). At the mid-test, the IQ scores of the TP group were lower than the AS group (P < 0.05, [95% CI -12.45 to -0.96], ES = 0.89). Additionally, at post-test, the IQ scores of the TP group were significantly lower than those of both AS (P < 0.01, [95% CI -14.12 to -2.74], ES = 1.15) and IS groups (P < 0.01, [95% CI -12.53 to -3.31], ES = 1.21). Swimming enhances children's balance and IQ scores more than traditional physical exercises. Involving parents in swimming leads to a more significant increase in IQ scores within 4 weeks of initial swimming exercise.